Testing, modeling, and design of square CFST columns internally reinforced by pultruded CFRP profile under axial compression. (15th December 2022) - Li, Guochang; Liu, Xinhe; Yang, Zhijian; Fang, Chen; Ge, Hanbin; Liu, Yaopeng
Highlights: Development of SCFST stub column internally reinforced by CFRP profile. Axial compression tests on 10 SCFST-CFRP columns and 2 SCFST columns. Study of mechanical properties of SCFST-CFRP column with varying parameters. Evaluation of existing design codes of AIJ, EC4, AISC-LRFD, and GB50936. Development of empirical equations for column axial load capacity. Abstract: This paper presents experimental and numerical investigations of an innovative composite column, which is formed using a square concrete filled steel tubular (SCFST) column internally reinforced by a carbon fiber reinforced polymer (CFRP) profile (referred to as SCFST-CFRP column), under axial compression. Full-scale axial compression tests were conducted on ten SCFST-CFRP columns with different steel ratios and steel grades and two traditional SCFST columns. The test results, including failure mode, axial load–displacement response, and strain development, were analyzed to examine the column behavior under axial compression. Numerical models of SCFST-CFRP columns were developed and validated to further investigate the stress distribution and load-bearing contribution of each column component. The validated models were then used for parametric studies that evaluated the effects of material and structural parameters on column behavior and axial load capacity. Besides, design rules, as suggested in the codes of AIJ, EC4, AISC-LRFD, and GB50936, were evaluated using experimental and numerical data for axially loaded SCFST-CFRP columns. In addition, empirical equations were developed through unified criteria to predict the SCFST-CFRP column capacity under axial compression.